2016
DOI: 10.1186/s13014-016-0627-5
|View full text |Cite
|
Sign up to set email alerts
|

Early detection and prediction of cardiotoxicity after radiation therapy for breast cancer: the BACCARAT prospective cohort study

Abstract: BackgroundRadiotherapy (RT) for breast cancer presents a benefit in terms of reducing local recurrence and deaths resulting from breast cancer but it can lead to secondary effects due to the presence of neighboring cardiac normal tissues within the irradiation field. Breast RT has been shown to be associated with long-term increased risk of heart failure, coronary artery disease, myocardial infarction and finally cardiovascular death more than 10 years after RT. However, there is still a lack of knowledge for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 42 publications
0
54
0
Order By: Relevance
“…Different diagnostic methods—including measurements of functional myocardial dysfunction, including strain and strain rate based on 2D‐speckle tracking echocardiography; anatomical coronary lesions including description of plaques in segments of coronary arteries based on coronary computed tomography angiography; and a wide panel of circulating biomarkers—might be useful options to detect early cardiotoxicity related to RT. Although modern RT has decreased the risk of cardiac mortality, the risk still exists even if mean doses have decreased, and it is important to continue efforts in radiation protection of healthy tissues neighboring RT‐treated organs …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different diagnostic methods—including measurements of functional myocardial dysfunction, including strain and strain rate based on 2D‐speckle tracking echocardiography; anatomical coronary lesions including description of plaques in segments of coronary arteries based on coronary computed tomography angiography; and a wide panel of circulating biomarkers—might be useful options to detect early cardiotoxicity related to RT. Although modern RT has decreased the risk of cardiac mortality, the risk still exists even if mean doses have decreased, and it is important to continue efforts in radiation protection of healthy tissues neighboring RT‐treated organs …”
Section: Discussionmentioning
confidence: 99%
“…Although modern RT has decreased the risk of cardiac mortality, the risk still exists even if mean doses have decreased, and it is important to continue efforts in radiation protection of healthy tissues neighboring RT-treated organs. 31…”
Section: Discussionmentioning
confidence: 99%
“…While in previous clinical studies, mean heart dose was related to the likelihood of RIHD [12], and the risk of major coronary events in breast cancer patients increased linearly by approximately 4-16% for each 1 Gy in mean heart dose received [6,9,10], other studies have shown that dose to the coronary arteries may also be an indicator of risk of developing coronary artery stenosis, an important aspect of RIHD [73]. Thus, there is a need for irradiation of small segments of the heart in pre-clinical models, which may include key sections of coronary arteries, to accurately predict risk factors and successfully develop interventions in RIHD [64,[74][75][76][77][78]. Partial heart irradiation in small animals may also be used to elucidate ways in which high-dose radiation treatment of segments of the heart can decrease ventricular tachycardia events in patients [79].…”
Section: Target Volume and Methods Of Radiation Delivery In Preclinicmentioning
confidence: 99%
“…Recent data suggest, that even lower radiation doses to the heart may play a relevant role for the development of late cardiac toxicity after breast cancer treatment [68]. Radiation exposure of the heart can result in coronary artery disease, congestive heart failure, valvular heart disease, pericardial disease, conduction abnormalities and sudden cardiac death [9].…”
Section: Introductionmentioning
confidence: 99%